Anti-tuberculosis drug induced hepatotoxicity: a study from Himalayan region - Gupta, Vipul; Guleria, Trilok C.; Kumar, Sanjay; Sharma, Subhash; Singh, Harjitpal; Kaur, Ravinder (International Journal of Research in Medical Sciences, 2022)
Background: Tuberculosis (TB) is the infection of global health concern. The management of TB is a 6-month course of anti-TB drugs. Compliance is crucial for curing TB. Adverse effects often affect the compliance negatively. One of the adverse effects affecting TB treatment outcome is anti-TB drug induced hepatotoxicity (DIH). Therefore, the purpose of this study was to assess the incidence of anti-TB DIH and its associated factors among newly diagnosed TB patients. Methods: A single centre prospective study was conducted from January-December 2020. All patients who were newly-diagnosed for TB, started anti-TB medication and diagnosed with drug-induced liver injury during anti-tubercular treatment included in the study. Results: Total of four hundred and ninety-two (492) TB patients taking anti-TB drugs were involved in this study with male predominance and maximum in the age group of 30-45 years. Smear-positive pulmonary TB accounted for 66.9% of all cases. During the study period, 9.3% TB patients developed anti-TB DIH. Among the cases of anti-TB DIH, female patients account for 52%. Patients with extra-pulmonary TB (n=23), low BMI (n=16), alcohol consumption (n=21) had developed anti-TB DIH. The time interval from the initiation of treatment to the onset of hepatotoxicity was 16-45 days. Conclusion: The chances of hepatotoxicity among TB patients taking anti-TB drugs are always there. Thus, it is necessary to monitor liver function in patients receiving anti-TB drugs routinely.